Associations between social determinants of health and 10‐year change in everyday functioning within Black/African American and White older adults enrolled in ACTIVE. Issue 1 (9th December 2022) - Clark, Alexandra L.; Weigand, Alexandra J.; Clay, Olivio J.; Owens, Joshua; Fiala, Jacob; Crowe, Michael; Marsiske, Michael; Thomas, Kelsey R.
Abstract: Introduction: Given prior work showing racial differences on baseline social determinants of health (SDoH) and 10‐year trajectories of everyday functioning, we examined associations between SDoH and longitudinal everyday functioning performance in Black/African American and White older adults. Methods: Participants were 2505 older adults (Mage = 73.5; 28% Black/African American) without dementia. SDoH included economic stability/status, education access/quality, health‐care access, neighborhood/built environment, and social/community contexts. The Observed Tasks of Daily Living (OTDL) measured everyday functioning and was administered at baseline and 1‐, 2‐, 3‐, 5‐, and 10‐year visits. Results: Across the sample, social and community context and economic stability/status were associated with steeper age‐related OTDL declines (βs = 0.05 to 0.07, P s < 0.001). Lower levels of social and community context (β = 0.08, P = 0.002) and economic stability/status (β = 0.07, P = 0.04) were associated with OTDL linear age declines in Black/African American participants, but not in White participants ( P s > 0.30). Discussion: Inequities across SDoH accelerate age‐related declines in everyday functioning among Black/African American older adults.